The Effect of Clustering Technique on Students` Writing Descriptive Text Ability (at the Nine Grade of SMP N 1 Marancar in 2020/2021)". - Sukriani Harahap (JURNAL LINER (Language Intelligence and Educational Research), 2021)
THE EFFECT OF CLUSTERING TECHNIQUE ON STUDENTS` WRITING DESCRIPTIVE TEXT ABILITY AT THE NINTH GRADE OF SMP N 1 MARANCAR IN 2020/2021 ACADEMIC YEAR Sukriani Harahap1, Kamisah2, Nina Nurbaidah3 Institut Pendidikan Tapanuli Selatan (IPTS) Email:sukriani.hrp8@gmail.com Abstract: The purposes of this research are to know: 1) The application of Clustering technique in writing descriptive text ability at the ninth grade of SMP Negeri 1 Marancar, 2) The Students’ writing descriptive text ability before and after using Clustering technique at the ninth grade of SMP Negeri 1 Marancar, 3) There is a significant effect of using Clustering technique at the ninth grade of SMP Negeri 1 Marancar. Method of the research was experimental with one group pre-test and post-test design.The population of this research at the ninth grade students of SMP Negeri 1 Marancar which consists of 100 students. The researcher used purposive sampling to get the sample it consists of 26 students. The techniques of collecting data were observation sheet and test.The result mean score of the application of Clustering technique was 3.6, it is categorized “very good”. The result showed score of students` before using Clustering technique was 49.69, it is categorized “ less”. Then, the result after using Clustering technique is 80 it is categorized “very good”. The result of t test is 4.74 and t table is 2.06. It means that there is a significant effect of using Clustering technique on students’ writing descriptive text ability at the ninth grade of SMP Negeri 1 Marancarin 2020/2021 Academic Year. Keyword : Clustering technique, Writing, Descriptive Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui: 1) Penerapan teknik Clustering dalam kemampuan menulis teks deskriptif pada siswa kelas sembilan SMP Negeri 1 Marancar 2) Kemampuan menulis teks deskriptif siswa sebelum dan sesudah menggunakan teknik Clustering pada siswa kelas sembilan SMP Negeri 1 Marancar 3) Ada pengaruh yang signifikan penggunaan teknik Clustering pada siswa kelas sembilan SMP Negeri 1 Marancar. Metode penelitian ini adalah eksperimental dengan rancangan one group pre-test dan post-test. Populasi penelitian ini adalah siswa kelas sembilan SMP Negeri 1 Marancar yang berjumlah 100 siswa. Pengambilan sampel menggunakan purposive sampling yang berjumlah 26 siswa. Teknik pengumpulan data menggunakan lembar observasi dan tes. Hasil rata-rata skor penerapan teknik Clustering adalah 3,6 dengan kategori “sangat baik”. Hasil penelitian menunjukkan skor siswa sebelum menggunakan teknik Clustering adalah 49,69 termasuk kategori “kurang”. Kemudian hasil setelah menggunakan teknik Clustering yaitu 80 dikategorikan “sangat baik”. Hasil uji t-test adalah 4,74 dan t tabel 2,06. Artinya ada pengaruh yang signifikan penggunaan teknik Clustering terhadap kemampuan menulis teks deskriptif siswa kelas XI SMP Negeri 1 Marancarin Tahun Pelajaran 2020/2021. Kata kunci: Clustering Technique, Menulis, Deskriptif. INTRODUCTION Writing is a subject that must be learned by students in every level of education. but most of the students still difficult in the understanding of writing, especially at the ninth grade students of SMP Negeri 1 Marancar. They were still hard to write a text, namely descriptive text. In fact, many students at the ninth grade of SMP Negeri 1 Marancar were not successful in writing descriptive text. It can be seen from the average score of pre-test when the researcher takes the preliminary data is 49,69. The researcher tried to give away of teaching descriptive text through the clustering technique. The clustering technique is one of the pre-writing techniques that can be implemented to help the students to generate their idea before starting to write. Based on the explanation above, the researcher is interested in conducting research to entitled “The Effect of Clustering Technique on Students` Writing Descriptive Text Ability (at the Ninth Grade of SMP N 1 Marancar in 2020/2021 Academic Year)”. Definition of Writing Writing is one skill that must be learned and mastered by students. According to Mertens (2010: 2), “Writing is indeed one of the most effortful activities that humans can implement”. Furthermore, Amarain et al, (2009: 28), “Descriptive is in all form of writing to create a vivid impression of a person, place, object or event”. According to brown in Sarwanti (2015: 23), there are five indicators of writing descriptive text such as content, organization, vocabulary, grammar, and mechanics. Content is there are least two things which can be measured in connection with content; the points that are presented and formal signals given the reader to guide in understanding the topic fully. organization is the process of organizing materials in writing involves coherence, the order of importance, general specific, specific to general, chronological order and special order pattern. Vocabulary is also a factor that can measure a person's ability to speak English.Grammar is one important component in writing. Mechanics of writing deals with capitalization, spelling, and punction. Definition of Clustering Technique Clustering is almost like drawing a map, using circles, lines, arrows and words. According to Scarry (2010: 8), “Clustering another brainstorming activity that you can use to generate ideas”. There are some steps of Clustering technique that must be followed to get the best result and suitable with the expectation. According to Maede in Meisuri and Wahyuni (2015: 150), the steps of clustering technique are: 1) Write a word or phrase on a clean piece of paper, 2) Circle the word and let connections flow, writing down each new word or phrase that comes to mind, circling it, and connecting it with a line, 3) Keep the hand moving all the time, 4) Cluster for a while, 5) Continue adding to the cluster, 6) Write a piece without worrying about perfection. Every method has their advantages when applied in teaching and learning English. According to Setyati in Meisuri and Wahyuni (2015: 151) there are some advantages in the clustering technique : 1) Reduced single points of failure functionality, 2) Ability to perform maintenance and upgrades with limited downtime, 3) Ability to easily scale up your cluster. While, the disadvantages of According to Setiyati in Meisuri and Wahyuni (2015: 151) the disadvantages can be seen follows 1) is not a good technique when it used to write an essay writing which has long paragraph, 2) The writing technique sometimes makes the learner are confused how to use it because the learners confused how to start to write, 3) The learners do this way under pressure to make this technique as an effective. METHODOLOGY OF THE RESEARCH The methodology of research is a way that is used by the researcher to collect the data in the field. According to Trianto (2010: 194), the Methodology of the research describes the plan of the research that consists of the procedure or the steps that must be done, time of the research, data resources, and how the data is acquired and analyzed. This research used experimental method with pre-experimental research design; one group pre-test post test design. In collecting data with one group pre-test post test design, the research used test and observation sheet as the instrument. The test is used to measured the students’ writing descriptive text ability and the observation sheet is used to observe the researcher in applied Clustering Technique. The research used quantitative data which is gotten by the researcher from calculating mean, median, and mode score from the test of writing ability and observation sheet of Clustering Technique. In analyzing the data, the researcher used ttest formula to look for the significant effect of clustering technique on students’ writing descriptive text ability. III. RESULT Based on the result obtained from the analysis of observation sheet about the application of at the ninth grade students of SMP Negeri 1 Marancar, the average score was 3.6 and it is categorized in “very good” criterion. The mean score of the students’ writing descriptive text ability before using Clustering Technique is 49.69. It is categorized as “less”. While, after using Clustering Technique, the mean score of the students’ writing descriptive text ability is 80. It is categorized as “very good” From the histogram above, the researcher concludes that posttest is higher that pretest and the researcher found that ttest is higher that ttable (4.74 > 2.06). It mens that there is a significant effect of Clustering technique on students’ writing descriptive text ability at the ninth grade students of SMP Negeri 1 Marancar in 2020/2021 Academic Year. DISCUSSION Based on the result of observation sheet in applying Clustering Technique, the researcher found that the score was 3.6. It is categorized as “very good criterion”. The result of average score of students’ writing descriptive text ability before taught by using Clustering Technique was 49.69. It is categorized as “less” criterion. Furthermore, the average score of students’ writing descriptive text ability after using Clustering Technique was 80. It is categorized as “Very good” criterion. It means that there is an improvement of students’ writing descriptive text ability after using Clustering Technique. Then, the result of ttest is higher thanttable (4.74 > 2.06). So, the hypothesis is accepted. The researcher concludes that the students’ writing descriptive text ability is higher after using Clustering Technique than before using it at the ninth grade students of SMK Negeri 1 Marancar. CONCLUSION The conclusion are: 1) The result of the application of Clustering technique in teaching writing descriptive text at the ninth grade students of SMP Negeri 1 Marancarin 2020/2021 Academic Year is 3.6 and it is categorized “Very Good”. It means that the researcher had applied Clustering technique in teaching writing descriptive text well. 2) The students’ writing descriptive text ability before taught by using Clustering technique at the ninth grade students of SMP Negeri 1 Marancar in 2020/2021 Academic Year was 49,69 and it is included as “Less” category. While, the students’ writing descriptive text ability after taught by using Clustering technique at the ninth grade students of SMP Negeri 1 Marancarin 2020/2021 Academic Year is 80 and it is included as “Good” category. 3) The testing that has been done to measure the hypothesis showed that ttest is higher than ttable (ttest 4.74> ttable 2.06). So, the alternative hypothesis of this research can be accepted. It means that there is a significant effect of Clustering technique on students’ writing descriptive text ability at the ninth grade students of SMP Negeri 1 Marancar in 2020/2021 Academic Year. REFERENCES Amarain, Shirin et al. 2009. Text Forms and Features: A Resource for International Teaching. Indonesia: Umbrella Corporation Meisuri, Sri Wahyuni. 2015.The Influence of Using Clustering Technique Towards Students’ Exposition paragraph writing Ability at The Second Semester of The Tenth Grade of MAN 1 Tanggamus in 2015/2016 Academic Year Mertens, Nathan L. 2010. Writing Proceses, Tools and Technique. New York: Education in a Competitive and Globalizing World. Nasution, Rafika Dewi et al. 2013. Reading. Medan. Unimed Press. . Sarwanti, Sri. 2015. Authentic Assestment in Writing. Transformatica. Vol II.No. 2 ISSN:0852-8412. Scarry, Sandra and Jhon. 2010. The Researcher’s Workplace with Readings.Building Collage Writing Skills. Seventh Edition. Wadsworth Cengage Learning.. Trianto. 2010. Pengantar Penelitian Pendidikan Bagi Pengembangan Profesi pendidikan dan Tenaga Kependidikan. Jakarta: Kencana.